Optimizing Child Part Inventory Management Using ABC Analysis and Safety Stock Calculation at PT ZYX - Adien, Aisyah Nurfadillah; Nisah, Firda Ainun (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
Efficient inventory management is essential for facilitating seamless manufacturing at PT ZYX, especially in managing child part stocks from several vendors. Suboptimal inventory management may result in stock deficits or surpluses, affecting production continuity and operational expenses. This study seeks to evaluate kid part inventory according to its strategic significance and establish safety stock levels for category A goods. The ABC classification approach was utilized to categorize inventory according to significance, and safety stock analysis was performed to determine ideal stock levels for essential items. The findings reveal that among 35 child components, 8 things are classified as category A, 4 items as category B, and 23 items as category C. The maximum safety stock value was identified in child component ID 70025 at 2,891 pieces, whilst the minimum was recorded for ID 70002 at 248 pieces. These findings offer a systematic inventory management strategy that enables the organization to enhance stock control, reduce expenses, and increase operational efficiency. The adoption of ABC categorization and safety stock analysis is anticipated to improve inventory management, facilitating a more efficient supply chain and superior resource allocation.